PENGARUH KOMUNIKASI DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA MASA PANDEMI COVID-19 DI BAGIAN PROTOKOL DAN KOMUNIKASI PIMPINAN SEKRETARIAT DAERAH KOTA BANDAR LAMPUNG - M Amsyar Riendika; Budhi Waskito (e-JKPP, 2022)
Improving the quality of human resources will have an impact on progress for the government to survive changes and competition in the sometimes unstable sphere of government. Another problem is the spotlight on the performance of bureaucracy in organizing public services, where during this pandemic the government is considered to have low performance in providing services to the community. This is also felt by the Protocol and Communication Section of the City Leader of Bandar Lampung. Based on observations made in the Protocol and Communication Section of the Head of the Bandar Lampung City Secretariat by looking at employee performance as a benchmark in research shows that the performance of employees has not been achieved optimally due to the number of employees who contracted the virus and decreased work motivation.This research aims to identify and analyze how much Communication, and Motivation affect Employee Performance during the Covid-19 Pandemic in the Protocol and Communication Section of the Bandar Lampung City Regional Secretariat. The research method used in this research is quantitative data analysis. Can be concluded, as follows: Problem sources, problem formulations, relevant concepts and theories and relevant discoveries, Hypothesis submissions, research methods, compiling research instruments, and conclusions.Based on the results of the above research, it can be taken a conclusion as follows: Communication has a significant effect on employee performance from the results of partial hypothesis tests in can the value of t calculate communication variables included in a high classification that means significant effect. Work Motivation has a significant effect on employee performance from the results of hypothetical tests partially in can the value of t calculate the variable Motivation included in the moderate classification (sufficient) which means a significant effect. Communication and Motivation work together have a significant effect on employee performance from the results of hypothesis tests simultaneously expressed accepted by other words accepting the hypothesis (Ha) and rejecting the hypothesis (Ho) has a mutual effect on employee performance.